Essays on the Corporate Governance Evolution and South African Real Estate Investment Trusts (REITs) - Moloi, Nosipho (University of the Witwatersrand, Johannesburg, 2024)
There has been substantial attention on corporate governance globally, representing a key area of research interest. Focusing on REITs as a natural experiment to study corporate governance and disclosure polices in SA is distinctive, particularly in that results are mixed globally. Studies by Campbell et al. (2011), Chong et al. (2016), and Chong et al. (2017) found an optimistic association with corporations that adopt CG and profitability; however, Bianco et al. (2007) and Bauer et al. (2010) reported adverse results. The study conducts three separate empirical studies that cover the following aspects of REITs: (a) the impact of corporate governance and corporate social responsibility on SA REITs performance; (b) the impact of corporate governance and foreign investor trading: An SA REIT perspective; (c) Black Economic Empowerment (BEE) and its influence on SA REIT liquidity. This thesis consists of three independent essays. The first essay employs a Corporate Governance Index (CGI) formulated from the King III and King IV reports to investigate the link concerning corporate performance and superiority of CG and the corporate social responsibility (CSR) of SA REITs listed on the Johannesburg Stock Exchange (JSE). The CGI index is created from the King III and IV reports to measure the compliance of 33 SA REITs listed on the JSE as of January 2023. These REITs are assessed from 2013. The empirical investigation using multiple correspondence analysis (MCA) reveals that CG practices have a positive influence on firms’ performance (such as total share return and return on assets). The results imply that CG’s standard principles influence the performance of firms’ SA REITs with a higher magnitude. Managers and investors that observe CG principles will notice improved firm performance. The CSR index is created from the King reports, and MCA was used to analyse CSR compliance to determine that SA REITs, which comply with CSR regulations, will improve returns. The second essay investigates CG and foreign investment activity of SA REITs. REITs offer a natural experiment in CG. These leave little cash flow for management, thereby reducing agency problems. A CGI Index was formulated from the King III and IV reports to examine the association concerning foreign investment and the quality of CG. A sample of 33 SA REITs from 2013 until 2022 is documented. The study adopted the unique multiple correspondence analysis (MCA) to form a matrix for the CG, and the foreign investment was formulated by adopting the Buy and Sell Index (BSI) to capture foreign investment. With a well-balanced panel, it was found that corporate governance (CG) significantly influences foreign investment with a greater magnitude. Additionally, SA REITs that are cross-listed with better CG in place 10 were documented as this has been linked with attracting more foreign investors. Due to the nature and effectiveness of the CG and the lack of this type of investigation in South Africa (SA), this study will inform SA REITs and policy makers in understanding the importance of complying with CG and the practical implications for its influences on foreign investment activity. The third essay examines the liquidity of SA REITs and their relationship to the BEE score. The contribution of this section to the literature is on SA REIT liquidity and its relationship with BEE policy. Firm liquidity has long been an area of interest of research (Yun, 2009). The paper adopts the BEE score for all SA REITs to measure their compliance levels and the link to a REIT liquidity. Thirty-three REITs are adopted from 2013 until 2022. To capture the different dimensions of a securitised REIT, more than one liquidity measure is used. This analysis uses four proxies to calculate REIT liquidity using ordinary least squares models (OLS). The study finds that the BEE has a positive association with an SA REIT liquidity, implying that REITs that comply with BEE policy are likely to have improved liquidity. Complying with government policy has been linked with firms’ good financial standing. Highly compliant REITs wanting to maintain their liquidity levels should consider the influence of the macro-economic factors, particularly the adverse relationships that negatively affect REIT liquidity such as employment levels. This is the first study to probe the BEE and REIT liquidity in the South African context.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment , School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; CORPORATE GOVERNANCE; REITS; CORPORATE SOCIAL RESPONSIBILITY; PERFORMANCE; FOREIGN INVESTMENT; BLACK ECONOMIC EMPOWEREMENT; SDG-8: Decent work and economic growth